CHALLENGES IN INTEGRATING A VIRTUAL PROJECT OFFICE: A SURVEY OF HIGH-TECH ENTERPRISES IN THE REPUBLIC OF BULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The publication deals with a current problem related to the challenges of integrating a virtual project office into the business activities of high-tech enterprises in the IT industry in the Republic of Bulgaria. Multi-layered emphasis has been placed, which is applied in a practical study, so as to establish the role of technology and the human factors in a digitalizing project environment. The survey emphasizes the opportunities for integrating a virtual project office, by studying a certain number of small and medium-sized high-tech enterprises in order to establish the main challenges. A survey has been conducted and an expert assessment method has been applied, through which empirical data has been generated in the business of small and medium-sized high-tech enterprises in the IT industry. Complex challenges and some management problems have been identified that affect the project activities of the studied enterprises in the integration of a virtual project office.